Biomechanical Basis of Interval Throwing Programs for Baseball Pitchers: A Systematic Review - Travis Dias; Benjamin G. Lerch; Jonathan S. Slowik; Kevin E. Wilk; James R. Andrews; E. Lyle Cain; Glenn S. Fleisig (International Journal of Sports Physical Therapy)
# Background